ANALISIS STATUS GIZI TERHADAP TUMBUH KEMBANG ANAK USIA DINI 4 – 6 TAHUN DI TK CANDRA JAYA JAKARTA BARAT - Liauw Leniwati (STKIP ROKANIA, 2021)
The results showed that the Body Weight Indicator (88) researchers used as information material to assess the state of good nutrition, growth and health of children in the research that the researchers conducted after measuring the child's weight there were 2 female students with weight entered in the classification of over nutrition and 2 female students and 1 male student with underweight nutritional classification. Body Height Indicator (18) is also very important, the advantage of this TB indicator is that the measurements are objective and repeatable, the tools can be made by themselves, cheap and easy to carry, the results of the researchers' measurements are used as a comparison of relative changes